2014
DOI: 10.1074/jbc.m113.532952
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β Signaling Participates in the Maintenance of the Primordial Follicle Pool in the Mouse Ovary

Abstract: Background: Why only a few follicles are activated to enter the growing follicle pool each wave remains unclear. Results: TGF-␤ regulates oocyte growth through p70 S6 kinase 1/ribosomal protein S6 signaling. Conclusion: TGF-␤ participates in maintenance of the primordial follicle pool. Significance: Learning how TGF-␤ acts on primordial follicle growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…The sections were counterstained with hematoxylin, dehydrated, coverslipped with histomount reagent, and imaged using BMI4000B downright microscope (Leica). The number of proliferating pre-granulosa cells was counted in 2 serial sections of the largest cross-section of each ovary and was averaged, as described previously46.…”
Section: Methodsmentioning
confidence: 99%
“…The sections were counterstained with hematoxylin, dehydrated, coverslipped with histomount reagent, and imaged using BMI4000B downright microscope (Leica). The number of proliferating pre-granulosa cells was counted in 2 serial sections of the largest cross-section of each ovary and was averaged, as described previously46.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of both Tsc2 and Tsc1 caused premature activation of all PFs around the time of puberty due to elevated mTORC1 activity in oocytes, leading finally to POF. Using a mouse fetal ovary culture system, Wang et al (2014) demonstrated the role of TGFb in maintenance of the PF pool and regulating oocyte growth through activation of rpS6, but not via activation of Akt or Foxo3a.…”
Section: Pi3k/pten/akt and Tsc/mtor Pathwaysmentioning
confidence: 99%
“…Appropriate expression of TGF‐β1 and TGF‐β receptor 1(TGF‐βR1) in the ovary promotes growth and differentiation of follicles as well as proliferation of ovarian granulosa cells . Overexpression of TGF‐β1 inhibits 17‐α hydroxylase activity through a direct non‐competitive mechanism, increases androgen synthesis, causes endocrine disorders, and further inhibits the growth and development of follicles, causing follicular dysplasia . In our experiments, TGF‐β1 and TGF‐βR1 expression were significantly increased by nano TiO 2 , resulting in excess production of androgen in theca cells and disorders in growth, development, proliferation, and maturation of follicles in female mice.…”
Section: Discussionmentioning
confidence: 66%
“…Transforming growth factor‐beta (TGF‐β) family members are clearly involved in regulation of ovarian function and follicular development . In particular, the TGF‐β pathway has been shown to regulate the development and apoptosis of primordial follicles through synergistic effects of PI3K/AKT/mT0R signaling and downstream regulation of the AKT/p70S6K‐rpS6/TSC/mTOR pathway, thus delaying POF …”
Section: Introductionmentioning
confidence: 99%